In vivo assessment of intratumoral aspirin injection to treat hepatic tumors - Saad-Hossne, Rogério [UNESP]; Teixeira, Fábio Vieira [UNESP]; Denadai, Rafael [UNESP] (Baishideng Publishing Group, 2013)
AIM: To study the antineoplastic efficacy of 10% aspirin intralesional injection on VX2 hepatic tumors in a rabbit model. METHODS: Thirty-two male rabbits (age: 6-9 wk; body weight: 1700-2500 g) were inoculated with VX2 hepatic tumor cells (104 cells/rabbit) via supraumbilical median laparotomy. On day 4 post-implantation, when the tumors were about 1 cm in diameter, the rabbits were randomly divided into the following groups (n = 8 each group) to assess early (24 h) and late (7 d) antineoplastic effects of intratumoral injection of 10% bicarbonate aspirin solution (experimental groups) in comparison to intratumoral injection of physiological saline solution (control groups): group 1, 24 h control; group 2, 24 h experimental; group 3, 7 d control; group 4, 7 d experimental. The serum biochemistry profile (measurements of glycemia, alkaline phosphatase, gamma-glutamyl transferase, aspartate aminotransferase, and alanine aminotransferase) and body weight measurements were obtained for all animals at the following time points: D0, before tumor implant; D4, day of treatment; D5, day of sacrifice for groups 1 and 2; D11, day of sacrifice for groups 3 and 4. Gross assessments of the abdominal and thoracic cavities were carried out upon sacrifice. The resected liver tissues, including hepatic tumors, were qualitatively (general morphology, signs of necrosis) and quantitatively (tumor area) assessed by histopathological analysis. RESULTS: Gross examination showed no alterations, besides the left hepatic lobe tumors, had occurred in the thoracic and abdominal cavities of any animal at any time point evaluated. However, the features of the tumor foci were distinctive between the groups. Compared to the control groups, which showed normal unabated tumor progression, the aspirin-treated groups showed imprecise but limited tumor boundaries and a general red-white coloration (indicating hemorrhaging) at 24 h post-treatment, and development of yellow-white areas of a cicatricial aspect at 7 d after treatment. At all time points evaluated, all except one biochemical parameters tested within the reference range (P > 0.05); a significant increase was detected in the alkaline phosphatase level of the control group 3 on D11 (P < 0.05). At 24 h post-treatment, the aspirintreated groups showed extensive coagulation necrosis accompanied by a remarkable absence of viable tumor foci; at 7 d after treatment, the tumors had completely disappeared in these animals and fibrous necrotic nodules had developed. In contrast, throughout the study course, the tumors of the control groups remained unchanged, showing tumor nodules without necrosis at the time point corresponding to 24 h post-treatment and increased amounts of tumor nodules at the time point corresponding to 7 d post-treatment. Quantitative analysis of the remaining tumor area revealed that the aspirin-treated groups had significantly smaller tumor foci at 24 h post-treatment (8.5% ± 0.7%) andat 7 d after treatment (11.0% ± 4.2%), compared to those in the control groups (24 h: 98.5% ± 1.5% and 7 d: 94.0% ± 2.7%; both, P < 0.005). CONCLUSION: Intralesional injection of a 10% aspirin solution causes destruction of VX2 hepatic tumors in rabbits without evidence of relapse at 7 d after treatment administration. © 2013 Baishideng.
Keywords: Antineoplastic; Aspirin; Hepatic tumor; Intralesional injection; Intratumoral injection; Rabbit; Therapy; VX2